Another man's poison - Sands, Leslie 1921-2001; Greenwood, John 1889-1975 (Cohen Film Collection LLC, 2014)
"In an isolated house, mystery writer Janet Frobisher is involved in potentially murderous relationships." [imdb.com]
Bildformat 4:3
Original: Großbritannien, USA 1951
Titelzusatz von DVD-Hülle: prepare for a twist you'll never see coming...
Keywords: Film; DVD-Video